Nutrition of Maasai Women and Children in relation to subsistence food production. - Nestel, P.S. (University of London, 1985)
A study of the causal relations between subsistence food production, food availability, food expenditure, food consumction and nutritional status was conducted in two different areas of Maasailand between July 1982 and June 1983. It involved 128 women and their 441 children/dependants divided among three different wealth groups. Anthropometric measurements, information on dietary habits and preferences and estimates of quantities of food consumed were recorded bimonthly. Between July 1983 and March 1984 3 day weighed and measured food intake and activity studies were conducted on a sub-sample of the above population in order to measure energy balances in both wet and dry seasons. Milk was the staple food of choice, its availability varied seasonally being heavily dependant on rainfall and the number of cattle owned. Purchased maizemeal was the alternative staple when insufficient milk was available. Other cereals, pulses and vegetables were rarely eaten but meat was consumed, its availability being related to that of dead or dying animals and to the timing of ceremonies. Protein intakes were approximately double the FAD recommended daily intakes (RDI) but energy intakes were deficient,especially in the drier areas arid toe rainy seasor,s arid were related to milk availabi1ity. There was no difference between wealth groups in the prevalence of chronic undernutrition suggesting that the inherent social mechanism of food gifting was important in bringing about a more equitable food distribution. Nutritional status deteriorated with age as children increasingly Undertook herding responsibilities which limited their access to food. After cirCUMcision, when they ceased herding, catch-up growth took place and adults reached normal stature. Past efforts to modernise Maasai society have focussed on animal production and have largely ignored social and cultural traditions r~lated to livestock use and food practices. Su~h traditions are fUndamental characteristics of Maasai society and unless this is taken into account the prospects for future change are likely to be li~ited.